Strategi Peningkatan Penjualan Produk Briket Kelurahan Indro Melalui Branding Packaging dan Marketing - Alma Dwi Yulia Sari; Muhammad Niqey Dzi Qolbin Saliem; Nikita Dinda Purnamasari; Wardatul Lailiyah; Sajidah Tiara Ayu Wiranda; Melanida Agustin; Tiara Nuriyah Sani; Avril Virga Mutiara Yasmin; Nur Rahmawati; Dhea Lailiya Rahma; Mechtildis Vanessa Caesarika (Pusat Riset dan Inovasi Nasional, 2024)
The problems often experienced by Small and Medium Enterpises (SMEs) in Indro Village are inappropriate marketing strategies and less attractive packaging. The aim of carrying out this Real Work Lecture (KKN) community service activity is to increase understanding of the importance of packaging and marketing aspects of charcoal briquette products among SMEs in Indro Village. In its implementation, it is carried out using a direct counseling and training method approach to SMEs actors which consists of four stages, namely observation, counseling, training and mentoring, and evaluation. From the evaluation results, it was found that the women in Indro Village already understood the material presented, and training and assistance for creative packaging could also be followed well. However, 4 out of 10 people experience difficulties in creating Instagram content. This is due to age and lack of familiarity with social media tools.